2020
DOI: 10.3390/microorganisms8020271
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Patterns of Crp on Monensin Biosynthesis in Streptomyces cinnamonensis

Abstract: Monensin, produced by Streptomyces cinnamonensis, is a polyether ionophore antibiotic widely used as a coccidiostat and a growth-promoting agent in agricultural industry. In this study, cyclic AMP receptor protein (Crp), the global transcription factor for regulation of monensin biosynthesis, was deciphered. The overexpression and antisense RNA silencing of crp revealed that Crp plays a positive role in monensin biosynthesis. RNA sequencing analysis indicated that Crp exhibited extensive regulatory effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…Crp deficiency retards growth, which is consistent with the phenotype of the adenylate cyclase (cya) mutant that cannot synthesize cAMP (Derouaux et al, 2004b). In addition to morphological development, recent studies have demonstrated that Crp regulates the synthesis of a range of secondary metabolites, such as actinomycin (Act), undecylprodigiosin (Red), and calcium-dependent antibiotic (CDA) in S. coelicolor (Gao et al, 2012), and monensin in Streptomyces cinnamonensis, by enhancing acyl-CoA precursors and upregulating the transcription of biosynthetic gene clusters (Lin et al, 2020).…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Crp deficiency retards growth, which is consistent with the phenotype of the adenylate cyclase (cya) mutant that cannot synthesize cAMP (Derouaux et al, 2004b). In addition to morphological development, recent studies have demonstrated that Crp regulates the synthesis of a range of secondary metabolites, such as actinomycin (Act), undecylprodigiosin (Red), and calcium-dependent antibiotic (CDA) in S. coelicolor (Gao et al, 2012), and monensin in Streptomyces cinnamonensis, by enhancing acyl-CoA precursors and upregulating the transcription of biosynthetic gene clusters (Lin et al, 2020).…”
Section: Introductionsupporting
confidence: 65%
“…The global regulator Crp protein regulates not only the core genes of the secondary metabolite biosynthetic gene cluster, but also the cluster-situated regulatory gene (monRI) in S. cinnamonensis (Lin et al, 2020). In S. roseosporus, dptR1, dptR2, and dptR3 are located adjacent to the dpt gene cluster, which leads to their description as potential cluster-situated regulators (Miao et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through this approach, a regulon of 12 transcriptional regulators of Streptomyces has been elucidated to date, including MtrA, 122 PhoU, 125 LmbU, 129 and Crp. 128 For instance, LmbU is a transcriptional regulator encoded in the lincomycin BGC of S. lincolnensis known as a pathway-specific regulator, that positively controls lincomycin production. Indeed, the lmbU deletion strain completely lost its lincomycin production ability.…”
Section: Comparative Transcriptomics For Understanding Regulation Of Secondary Metabolismmentioning
confidence: 99%
“… 2015a ) and to elucidate the regulatory role of the cyclic AMP receptor protein (Crp) in Streptomyces cinnamonensis by comparing the monensin yields and transcriptomic profiles between control, crp -overexpressing and crp -silencing strains (Lin et al . 2020 ). There is a pressing need for more extensive studies to identify sRNAs and elucidate their function in Streptomyces and other actinomycetes with a rich secondary metabolism.…”
Section: Regulatory Engineering: Srna As An Emerging Toolmentioning
confidence: 99%